Deployment experiences and mental health problems as predictors of post-deployment unemployment length: a prospective, register-based study among Danish soldiers. Issue 12 (7th December 2020) - Elrond, Andreas Friis; Conway, Paul Maurice; Andersen, Søren Bo; Karstoft, Karen-Inge; Vedtofte, Mia Sadowa; Pedersen, Jacob
Abstract : Objectives: To test responses of formerly deployed soldiers (FDS) to a questionnaire on deployment experiences in combination with screening levels of post-traumatic stress disorder (PTSD) and depression approximately 6 months after homecoming as predictors of the subsequent probability of gaining employment when unemployed within 5 years post-deployment. Design, setting and participants: Danish FDS responders (n=3935) and non-responders (n=3046) to a 6-month post-deployment screening questionnaire after returning from a first-ever deployment to Kosovo, Iraq or Afghanistan (2002 to 2012) were included in the study and followed in public registers from 6 months to 5 years post-deployment. Primary and secondary outcome measures: We tested Cox regression models including deployment experiences (1a), screening levels of PTSD and depressive symptoms (1b), and their combination (2) for FDS responders. For all FDS, a secondary model included a measure on whether they responded to the questionnaire (3). Results: Neither the deployment experiences (1a) of exposure to danger and combat (HR=1.00, 95% CI=0.97 to 1.03) and witnessing consequences of war (HR=1.01, 95% CI=0.96 to 1.06), or the screening levels (1b) of PTSD (HR=1.06, 95% CI=0.84 to 1.33) and depressive symptoms (HR=0.82, 95% CI=0.64 to 1.06) were significant predictors of transitioning from unemployment to employment. Similar results were found for the combined model (2). A tendency among non-respondents (3) to have a lower probability of transitioning from unemployment to employment was found (HR=0.90, 95% CI=0.81 to 1.00). Conclusion: Deployment experiences, PTSD and depressive symptoms, as measured at 6-month screening questionnaire, did not predict differences in the probability of gaining employment when unemployed within 5 years post-deployment. However, the findings suggest that those with the least probability of transitioning from unemployment to employment can be found among the non-responders to the post-deployment screening questionnaire.